Unveiling the effects of the secretome of mesenchymal progenitors from the umbilical cord in different neuronal cell populations - Fraga, J. S. (2013)
It has been previously shown that the secretome of Human Umbilical Cord Perivascular Cells (HUCPVCs), known for their mesenchymal like stem cell character, is able to increase the metabolic viability and hippocampal neuronal cell densities. However, due to the different micro-environments of the distinct brain regions it is important to study if neurons isolated from different areas have similar, or opposite, reactions when in the presence of HUCPVCs secretome (in the form of conditioned media-CM). In this work we: 1) studied how cortical and cerebellar neuronal primary cultures behaved when incubated with HUCPVCs CM and 2) characterized the differences between CM collected at two different conditioning time points. Primary cultures of cerebellar and cortical neurons were incubated with HUCPVCs CM (obtained 24 and 96 h after three days of culturing). HUCPVCs CM had a higher impact on the metabolic viability and proliferation of cortical cultures, than the cerebellar ones. Regarding neuronal cell densities it was observed that with 24 h CM condition there were higher number MAP-2 positive cells, a marker for fully differentiated neurons; this was, once again, more evident in cortical cultures. In an attempt to characterize the differences between the two conditioning time points a proteomics approach was followed, based on 2D Gel analysis followed by the identification of selected spots by tandem mass spectrometry. Results revealed important differences in proteins that have been previously related with phenomena such as neurl cell viability, proliferation and differentiation, namely 14-3-3, UCHL1, hsp70 and peroxiredoxin-6. In summary, we demonstrated differences on how neurons isolated from different brain regions react to HUCPVCs secretome and we have identified different proteins (14-3-3 and hsp70) in HUCPVCs CM that may explain the above-referred results.